2017
DOI: 10.1111/1758-2229.12525
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen availability on the activities of ammonia‐oxidizing archaea

Abstract: Recent studies point to the importance of oxygen (O ) in controlling the distribution and activity of marine ammonia-oxidizing archaea (AOA), one of the most abundant prokaryotes in the ocean. The AOA are associated with regions of low O tension in oceanic oxygen minimum zones (OMZs), and O availability is suggested to influence their production of the ozone-depleting greenhouse gas nitrous oxide (N O). We show that marine AOA available in pure culture sustain high ammonia oxidation activity at low μM O concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
96
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 56 publications
16
96
2
1
Order By: Relevance
“…We do not have a direct explanation for this effect, but it is possible that hydrogen peroxide has a negative effect on competitors of Thaumarchaea at these sites. This is supported by recent studies reported by Qin et al (), demonstrating that some AOA are resistant to extremely high peroxide concentrations (> 1 μ mol L −1 ). Thus, our data indicate that direct irradiation exerts a more fundamental control on ammonia oxidation, at least in open ocean regimes, and that H 2 O 2 would have a modest effect on ammonia oxidation within the mixed layer and a negligible effect below.…”
Section: Discussionsupporting
confidence: 87%
“…We do not have a direct explanation for this effect, but it is possible that hydrogen peroxide has a negative effect on competitors of Thaumarchaea at these sites. This is supported by recent studies reported by Qin et al (), demonstrating that some AOA are resistant to extremely high peroxide concentrations (> 1 μ mol L −1 ). Thus, our data indicate that direct irradiation exerts a more fundamental control on ammonia oxidation, at least in open ocean regimes, and that H 2 O 2 would have a modest effect on ammonia oxidation within the mixed layer and a negligible effect below.…”
Section: Discussionsupporting
confidence: 87%
“…Bakken, 1999;Shaw et al, 2006), due to differences in available NH + 4 and oxygen concentrations that affect enzymatic reactions. N 2 O yields from AOA cultures are below or in the lower range of those observed for AOB, that is, 0.04%-0.3%, and NH + 4 and oxygen concentration have no or little effect on yield Hink, Lycus, et al, 2017;Kim et al, 2012;Löscher et al, 2012;Santoro et al, 2011;Stieglmeier, Mooshammer, et al, 2014;Qin et al, 2017). An alternative explanation is redox balancing, in which electrons generated by hydroxylamine dehydrogenase are shuttled to denitrification enzymes when they exceed the capacity of terminal oxidases (Hink, Lycus, et al, 2017).…”
Section: Dis Tin C Tion Of Archae Al and Bac Terial N 2 O Produc Tionmentioning
confidence: 95%
“…The yield of N2O (molar ratio of N2O production to ammonium oxidation) increases with decreasing oxygen (Goreau et al, 1980). Culture (Qin et al, 2017) and field studies (Bristow et al, 2016;Peng et al, 2016) have shown high affinity of oxygen (< 5 μmol L -1 ) during ammonium oxidation. The main sources of ammonium in the Chesapeake Bay include remineralization of organic matter in the oxygenated water column and sediments (Kemp et al, 1990) and atmospheric deposition (Larsen et al, 15 2001).…”
Section: The Sensitivities To Increasing [O2] Of No2mentioning
confidence: 99%